Pengaruh Corporate Social Responsibility, Good Corporate Governance, Dan Ukuran Perusahaan Terhadap Kinerja Keuangan: Studi Empiris Pada Perusahaan BUMN Yang Terdaftar Di Indeks BUMN 20 Pada BEI Periode 2017-2021 - Fatimah, Siti Nur; Annisa, Dea (Institut Bisnis dan Informatika Kesatuan, 2023)
This study aims to examine and obtain empirical evidence regarding the influence of Corporate Social Responsibility, Good Corporate Governance and Firm Size on Financial Performance. The population in this study are state-owned companies listed on Index BUMN 20 on the Indonesia Stock Exchange for the period 2017 – 2021. The type of research being conducted is quantitative research using associative methods. Data collection techniques in this study are secondary data with data collection methods, namely documentation. The research sample was determined using a purposive sampling technique using eviews 9 software. The number of BUMN companies used as research samples was 10 companies with observations for 5 years. The analysis technique used is panel data regression. The results of the study prove that corporate social responsibility, managerial ownership as a GCG mechanism, institutional ownership as a GCG mechanism, and firm size simultaneously influence financial performance. Meanwhile, partially corporate social responsibility has no effect on financial performance, while managerial ownership as a GCG mechanism, institutional ownership as a GCG mechanism, and firm size have an effect on the company's financial performance